Labelling Hierarchy for Street Maps Using Centrality Measures - Shoman, Wasim; Gulgen, Fatih (TAYLOR & FRANCIS LTD, 2018)
This paper proposes a compound hierarchy to be used in cartographic labelling of streets. The main purposes of this hierarchy are to ease navigation of street maps and to provide more understandability and legibility of street features for map users. The hierarchy uses centrality measures along with functional classes of the streets to order features according to their spatial importance in each used zoom level. The calculation of a proper radius, to be employed in the calculations of centrality measures, is based on extracting proper field of view in the map user's focus status. The used measures are integrated using fuzzy-analytic hierarchy process, yielding proper coefficients to create the hierarchy. The hierarchy is applied for the thinning process and later for using the styled layer descriptor to label street features. Quality constrains are implemented to make the street labels more understandable and readable.
Keywords: Generalization; labelling; multi-resolution; street network; functional class; NETWORK ANALYSIS; FUZZY-AHP; SERVICES; Geography